Trench Etch Processing for SiC Superjunction Schottky Diodes - Cao, Qinze; Renz, Arne Benjamin; Gammon, Peter M.; Lophitis, Neophytos; Melnyk, Kyrylo; Antoniou, Marina (My University, 2025)
This study focuses on the trench etching process for the fabrication of SiC Superjunction Schottky diodes, utilizing an ICP-RIE technique. Through a series of experiments, we optimized the etching parameters, including ICP power, RF power, and SF6 gas flow rates, to achieve etching rates ranging from 157 nm/min to 372.1 nm/min. Additionally, the study identified the performance of the hard mask as a critical issue during the etching process, which was improved by reducing the RF power below 80 w. The deepest trench achieved reached a depth of 21 μm at 75 w RF power, 1000 w ICP power and 40 sccm SF6, confirming the feasibility of this approach for fabricating high-performance SiC superjunction devices.
Keywords: inductively coupled plasma and reactive ion etching; trench devices; Silicon carbide; Superjunction; Schottky Diode; superjunction; device fabrication